Why Communication will Make us Happy: Vocational Values of Prospective Communication Students - Hernández Franco, Vicente; Muñiz Velázquez, José Antonio; Nó Sánchez, Javier (Estudios sobre el Mensaje Periodístico, 2017)
Communication is still the first choice for many young people for their studies. What vocational interests and values are behind that choice? In other words, what do they expect to find in communication that it makes them happy in their future job? To find out, we studied the vocational profile and values of 5,889 high school sophomores. 469 of them showed preference towards the vocational area of communication. The most salient values in this group were: pursuing a fun occupation, dynamic and varied work tasks, entrepreneurship, fame and social status. By contrast, their values with lower averages, among others, were doing something important, helping people, and doing something useful and important with their work. This results, at least, deserve some reflection.